METHODS OF READING AND WRITING JAVANESE PUZZLES USING COMPUTER-BASED VISUAL MEDIA FOR ELEMENTARY SCHOOL STUDENTS - Setyawan, Bagus Wahyu; Rosyidiana, Hafidz; Hidayah, Sa'adatun Nuril; Puspita, Ayunda Riska (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2022)
Aksara Jawa is a form of Javanese culture that must be maintained, preserved from an early age. Learning to read and write Aksara Jawa must be taught from an early age so that students have a love for their own culture through Aksara Jawa. This research focuses on describing and explaining the use of puzzle game methods in the subject matter of reading and writing Aksara Jawa with computer-based visual media. The data sources in this study were obtained from literature studies and interviews with speakers. The data obtained are then analyzed with interactive and deductive analysis techniques. The data obtained are then analyzed with interactive and deductive analysis techniques. The results showed that a selection of innovative and creative learning methods was able to increase student motivation to follow the teaching and learning process. Teachers can use learning media to support the learning process of reading and writing Aksara Jawa to achieve learning objectives. With the puzzle game method applied with computer-based visual media, it is one of the uses of the right methods and media to achieve the goal of learning to read and write Aksara Jawa